CATEGORIZATION OF ISLAMIC THINKING - Syaripuddin Daulay (Journal Analytica Islamica, 2021)
Epistemology discusses the sources of knowledge and how to obtainknowledge. History has recorded that Islamic civilization was once the mecca ofworld knowledge around the 7th century to the 15th century. After that, thepackaging period began to become Malay, static, even backwards to the 21stcentury. The method used to obtain the data needed in this discussion is the LibraryResearch method. The result is that there are 3 (three) categorizations of Islamicthinking, namely Bayani epistemology, which is an epistemology which assumesthat the source of knowledge is revelation (text) or reasoning from the text. Burhaniepistemology is an epistemology which holds that the source of knowledge is reason.Meanwhile, the epistemology of 'irfani is an epistemology which assumes thatknowledge is the will (iradah). These three categories of thinking also have theirrespective advantages which of course can be used according to the problem orsituation at hand.